2014
DOI: 10.1002/jsfa.6630
|View full text |Cite
|
Sign up to set email alerts
|

Esterification of fatty acids by Penicillium crustosum lipase in a membrane reactor

Abstract: The confinement of lipase from P. crustosum in a membrane reactor was possible, resulting in the satisfactory conversion of butyric acid to ethyl butyrate with the possibility of reuse of the immobilized enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Although the remaining activity yielded decent conversion in our case, it poses a problem for its wider application as a cofactor recycling system. Other enzymes, such as glucose dehydrogenases [28], could be used for the recycling of the cofactor but complexity of the system is increased with the added substrate and product generated. To surpass this limitation, the use of other formate dehydrogenases, which pose the advantage of limited residues and excellent atom economy, capable to better withstand covalent immobilisation could greatly benefit the proposed system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the remaining activity yielded decent conversion in our case, it poses a problem for its wider application as a cofactor recycling system. Other enzymes, such as glucose dehydrogenases [28], could be used for the recycling of the cofactor but complexity of the system is increased with the added substrate and product generated. To surpass this limitation, the use of other formate dehydrogenases, which pose the advantage of limited residues and excellent atom economy, capable to better withstand covalent immobilisation could greatly benefit the proposed system.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, instead of covalently immobilising the enzyme, which normally causes a loss of activity due to increased rigidification, the enzymatic cocktail is placed inside a dialysis membrane. This allows the free flow of the substrate and product in and out of the membrane but avoids the loss of enzyme to the reaction bulk, allowing its reuse in subsequent reactions, even in continuous using membrane reactors [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that enzyme recycling by using membranes is an easy and feasible technique (Agustian et al 2011;Marques et al 2017;Nguyen et al 2014;Possebom et al 2014). Membranes with specific pore sizes are selected to retain or separate free or immobilized enzyme in the production medium.…”
Section: Introductionmentioning
confidence: 99%
“…According to the reaction type, polymeric, inorganic, ceramic, metallic materials can be used as membrane and these are simply characterized as porous or dense membrane [7][8][9][10]. Esterification, wastewater treatment, oxidation and hydrogen production are well known commercial CMR applications [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%